Engineering science - Edward Hughes (Longman, 1996)
The book offers comprehensive coverage of the basic principles of engineering science, including mechanics, heat, electricity and sound. It is supported throughout by numerous problems and worked examples, and there is a useful section on symbols and abbreviations